Gender-Neutral Bathrooms in Relation to Promoting Inclusivity: A QCU Students Perspective - Arnado, Janessa Joy O.; Coralde, Renalyn P.; Dagdag, Aubrey Jane P.; Lozano, Justine A.; Obar, Cindy Nicole C.; Barcela, Raul Beni (International Journal of Research in Interdisciplinary Studies, 2025)
This quantitative study investigates the impact of gender-neutral bathrooms implementation in college settings, focusing on perceptions, experiences, and outcomes among students. This study was conducted in Quezon City University with a total of 50 participants from the students of different colleges. Results indicate strong support among respondents for the presence of gender-neutral bathrooms, with a majority agreeing on their contribution to a more inclusive campus environment. However, despite this support, social barriers such as social stigma and institutional resistance pose challenges to the widespread implementation of gender-neutral facilities. While students recognize the benefits of gender-neutral bathrooms for diverse gender identities and expressions, there remains a need for greater education and advocacy to address misconceptions and facilitate institutional change. Findings highlight the need for continued education and advocacy to eliminate misconception and facilitate inclusive policies.